(untitled) (Research, Society and Development, 2023)
Adverse events caused by drugs affect patient safety in health institutions, so notification is a commitment factor on the part of health professionals to reduce the occurrence of errors. The aim is to analyze possible causes of underreporting of adverse drug events. The present work was carried out through a retrospective study with a quantitative and descriptive approach. The present study allowed the identification of points of improvement regarding the notification of adverse events caused by drugs that directly affect patient safety, allowing the knowledge of failures and problems of professionals and causes of underreporting, reducing the number of errors. Result: it was indicated that due to fear of punishment, shame, and lack of knowledge on the part of health professionals, they fail to notify the mistakes made. Anonymous practice should be encouraged, measures that guarantee the secrecy of those notifying, contributing to the increase in notifications.